Advances in enzymatic oxyfunctionalization of aliphatic compounds - Aranda, Carmen; Carro, Juan; González-Benjumea, Alejandro; Babot, Esteban D.; Olmedo, Andrés; Linde, Dolores; Martínez, Angel T.; Gutiérrez, Ana (Biotechnology advances, 2021)
Selective oxyfunctionalizations of aliphatic compounds are difficult chemical reactions, where enzymes can play an important role due to their stereo- and regio-selectivity and operation under mild reaction conditions. P450 monooxygenases are well-known biocatalysts that mediate oxyfunctionalization reactions in different living organisms (from bacteria to humans). Unspecific peroxygenases (UPOs), discovered in fungi, have arisen as “dream biocatalysts” of great biotechnological interest because they catalyze the oxyfunctionalization of aliphatic and aromatic compounds, avoiding the necessity of expensive cofactors and regeneration systems, and only depending on H2O2 for their catalysis. Here, we summarize recent advances in aliphatic oxyfunctionalization reactions by UPOs, as well as the molecular determinants of the enzyme structures responsible for their activities, emphasizing the differences found between well-known P450s and the novel fungal peroxygenases.